Constipation and Lower Urinary Tract Dysfunction in Children and Adolescents: A Population-Based Study - Sampaio, Clara; Sousa, Ariane Sampaio; Fraga, Luis Gustavo A.; Veiga, Maria Luiza; Bastos Netto, José Murillo; Barroso, Ubirajara (Frontiers in Pediatrics, 2016)
Objective: To evaluate the correlation between constipation and lower urinary tract dysfunction (LUTD) and nocturnal enuresis in a population-based study. Material and Methods: This is a cross-sectional study. The criteria for inclusion were: children and adolescents of between 5 and 17 years and who agreed to sign the informed consent form. The study excluded students with neurological problems or who had documented abnormalities of the urinary tract. To identify the presence and severity of LUTD, we used the Voiding Dysfunction Symptom Score (DVSS). To evaluate the presence of constipation, Rome III questionnaire was used. Results- We interviewed 829 children and adolescents, of which 416 (50.18%) were male. The mean (SD) age was 9.1 (± 2.9) years. The overall prevalence of LUTD was 9.1%, predominantly in girls (15% versus 3.1%, p < 0.001). Constipation was found in 9.4% of boys and 12.4% of girls (p = 0.169). Constipated children were 6.8 times more likely to have LUTD than those not constipated (p < 0.001, coefficient and correlation of 0.411). Constipation was found in 8.2% of children without LUTD and in 35.2% of children with LUTD. We performed multivariate analysis to identify urinary symptoms that are independent predictors of the presence of constipation. The presence of infrequent urination (p = 0.004) and holding maneuvers (p < 0.001) were independent predictors. It was noted also that constipated children, according to the Rome III criteria, possess a worse DVSS (p < 0.001). Regarding the presence of nocturnal enuresis, 12.6% of children and adolescents had constipation in association with this symptom. However, this relationship was not statistically significant (p = 0.483). Conclusion- Constipated children were 6.8 times more likely to have LUTD than those not constipated. Among the urinary symptoms, infrequent voiding and holding maneuvers are independent factors of urinary expressions in constipated children. Children with more severe constipation have more prominent urinary symptoms. The presence of enuresis was not associated to constipation.